Living with breathlessness in chronic heart failure: a qualitative study. Issue 13 (27th March 2017) - Walthall, Helen; Jenkinson, Crispin; Boulton, Mary
Abstract : Aims and objectives: To explore how patients with Chronic Heart Failure describe their experiences of breathlessness, the pattern of their breathlessness, how daily life is affected and how they adjust to and manage these symptoms. Background: Chronic Heart Failure is a highly prevalent syndrome often with poor outcomes and in a patient group who are predominately elderly. Breathlessness is the main symptom experienced by patients and often relates to decompensation and hospitalisation, yet subtle changes described by patients are often not discussed with health care professionals. Design: A descriptive qualitative design. Methods: Twenty‐five participants with heart failure with reduced ejection fraction (HF‐rEF) from a tertiary referral centre in England were recruited. Each participant took part in a semi‐structured interview exploring the effect of breathlessness had on their lives. Data was analysed through Braun and Clarke's framework for thematic analysis. Results: All participants reported experiencing breathlessness daily. Four sub‐themes were identified in their accounts: nature of breathlessness, emotional impact of breathlessness, impact of breathlessness on daily life and managing breathlessness. Conclusion: Participants were able to give vivid descriptions of breathlessness and the way it affected their lives. Relevance to clinical practice: Health care professionals need to take account of each patient's personal assessment of their own breathlessness and how this is having an effect on their life and ability to undertake activities of daily living. Self‐care management strategies need to be developed so that subtle changes can be assessed by the patient and reviewed by the healthcare professional to avoid hospitalisation and increased mortality risks.